Respuesta :

d)

[tex] \frac{2 {x}^{2} - xy + 2xy - {y}^{2} }{6xy - 3 {y}^{2} } = \frac{x(2x - y) + y(2x - y)}{3y(2x - y)} = \\ [/tex]

[tex] \frac{(x + y)(2x - y)}{3x(2x - y)} = \frac{x + y}{3x} \\ [/tex]

_________________________________

e)

I think -6 should be +6

or +3x should be -3x

[tex] \frac{ {x}^{2} + 2x + x + 2 }{ {x}^{2} + 2x + 3x + 6 } = \frac{x(x + 2) + (x + 2)}{x(x + 2) + 3(x + 2)} = \\ [/tex]

[tex] \frac{(x + 1)(x + 2)}{(x + 3)(x + 2)} = \frac{x + 1}{x + 3} \\ [/tex]

Or

[tex] \frac{x(x + 2) + (x + 2)}{x(x + 2) - 3(x + 2)} = \frac{(x + 1)(x + 2)}{(x - 3)(x + 2)} = \\ [/tex]

[tex] \frac{x + 1}{x - 3} \\ [/tex]

_________________________________

f)

[tex] \frac{ {a}^{2} - 5a - 4a + 20 }{ {a}^{2} - 5a + 2a - 10 } = \frac{a(a - 5) - 4(a - 5)}{a(a - 5) + 2(a - 5)} = \\ [/tex]

[tex] \frac{(a - 4)(a - 5)}{(a + 2)(a - 5)} = \frac{a - 4}{a + 2} \\ [/tex]

And we're done.

Thanks for watching buddy good luck.

♥️♥️♥️♥️